Surgery in renal cell cancer. Issue 3 (March 2015) - Blick, Christopher; Sullivan, Mark; Cranston, David
<x xml:space="preserve">Abstract</x> The incidence of renal cancer has increased over the past 30 years, with renal cell carcinoma being the most common form. In this article, the authors discuss the surgical options for treatment of both localised and metastatic renal cell carcinoma.